In the Name of Belief: Religious (In)tolerance, Hate Speech and Justice in Classical Greek and Roman Sources - Buis, Emiliano Jerónimo (2023)
Hate speech is far from a modern concept. In this chapter, I attempt to find some textual examples of these topics in classical Greece and ancient Rome, with the purpose of analysing them in a way that could be illuminating to understandthe current scope and limits of the modern notion of religious hate speech. Attention here will be limited to Greek and Roman civilizations in pre-Christian times, since other contributions in this volume will enlarge the temporalscope and include references to early Christian sources.